Litterfall production and nutrient deposition through leaf fallen in three tamaulipan thornscrub communities, north-eastern Mexico - López Hernández, Juan Manuel; Maiti, Ratikanta; Gómez Meza, Marco Vinicio; González Rodríguez, Humberto; Cantú Silva, Israel; Ramírez Lozano, Roque Gonzalo; Moreno Pando, Maricela; Estrada Castillón, Andrés Eduardo (2014)
Litterfall and the contents of macro- and micro-nutrients derived from its decomposition contribute greatly to the growth and productivity of forest ecosystem. The present study was undertaken to know the variability during two years in the deposition of litterfall and deposition of nutrients through leaf fallen litterfall in three sites of the state of Nuevo Leon (Los Ramones, China and Linares), north-eastern Mexico, which encompasses the Tamaulipan thornscrub plant community. The quantities of litterfall production and its constituents varied between 2009 and 2010, being the year 2010 where higher litterfall and nutrients occured. Mean litterfall production during the two years showed the following trend: Los Ramones (364.8), China (522.7) and Linares (583.1 g m-2 year-1). For leaf constituent, mean deposition ranged from 200.9 (Los Ramones) to 409.8 g m-2 year-1 (Linares), twigs from 62.4 (Los Ramones) to 89.3 (Linares), reproductive structures from 62.5 (Linares) to 80.3 (Los Ramones) and the miscellaneous component, constituted by unidentified plant material, body and insect feces, ranged from 21.1 (Linares) to 32.7 g m-2 year-1 (China). During the two years, mean annual deposition of Ca+K+Mg+P+N for Los Ramones, China and Linares was 10.1, 21.5 and 24.8 g m-2 year-1, respectively. Regardless of the research site, the order of macro and micro-nutrients deposition was as follows: Ca>N>K>Mg>P and Fe>Mn>Zn>Cu, respectively. There were spatial and temporal variations in litterfall deposition in terms of quantity, quality and potential nutrient returns. It is documented that the variability of litterfall and contents of nutrients derived from litterfall is influenced by the physioco-chemical characteristics of soils, diversity in vegetation and climatic conditions prevailing in different sites and years